2004
DOI: 10.3132/dvdr.2004.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndromes and diabetes mellitus

Abstract: P atients with diabetes mellitus who present with acute ST-segment elevation myocardial infarction or non-ST-segment elevation acute coronary syndromes have a higher risk of adverse outcomes than patients without diabetes, and appear to derive greater benefit from evidence-based therapies. However, patients with diabetes mellitus are less commonly treated with proven therapies, so renewed efforts are needed to improve the quality of care and outcomes for patients with diabetes mellitus who present with acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 79 publications
0
10
0
6
Order By: Relevance
“…We suggest that partial occlusion of the RCA promoted damage of the parasympathetic fibers of the right vagus, and was the cause of referred otalgia and pharyngitis in our patient. Sensory nerves are affected by type 2 diabetes [47], but whether such a preexisting condition predisposes a person to angina-referred otalgia or pharyngitis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that partial occlusion of the RCA promoted damage of the parasympathetic fibers of the right vagus, and was the cause of referred otalgia and pharyngitis in our patient. Sensory nerves are affected by type 2 diabetes [47], but whether such a preexisting condition predisposes a person to angina-referred otalgia or pharyngitis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Nessa subpopulação, predominam dispnéia, sudorese, náuseas e vômitos em relação à dor torácica (16), o que leva a um retardo na procura por serviços de emergência e, conseqüentemente, posterga o início do seu tratamento (17). A interpretação de eletrocardiogramas também é mais difícil nesses pacientes, visto que as sulfoniluréias, usadas no tratamento da hiperglicemia, parecem diminuir o grau de alterações eletrocardiográficas, por uma diminuição da sensibilidade do método, reduzindo a amplitude de alterações do segmento ST e onda T (18). Durante a internação, os diabéticos apresentam taxas mais elevadas de mortalidade que os não-diabéticos.…”
Section: Características Clínicas Das Síndromes Coronarianas Agudas Eunclassified
“…Several trials have consistently shown larger relative risk reductions for pharmacotherapies in the treatment of ACSs in diabetic patients versus nondiabetic patients. Because the absolute risk is larger in diabetic patients than in nondiabetic patients, the potential absolute benefit will also be larger in diabetic patients (10,11). This fact underscores the importance of using known evidencebased treatment for all ACS patients, especially diabetic patients.…”
mentioning
confidence: 94%